Geochemistry of Asara Shale member of Karaj Formation, Central Alborz, Iran: Provenance, source weathering and tectonic setting. (November 2020) - Malekzadeh, Mohammad; Hosseini-Barzi, Mahboubeh; Sadeghi, Abbas; Critelli, Salvatore
Abstract: The Asara Shale Member of the Karaj Formation, Middle to Upper Eocene in age, includes mixed volcaniclastic, siliciclastic and carbonate strata, in the Alborz Mountains, northern Iran. These strata have been geochemically analyzed to constrain their source area provenance. Most of the major and trace element contents of Asara Shale samples are generally similar to the upper continental crust (UCC) values and their chemical index of alteration (CIA) values (31.7–50.9), suggesting a semi-arid climate in a weathering-limited source area. Moreover, correlation of major element oxides suggests the controlling effect of plagioclase and clay minerals on these data when XRD analysis and SEM images indicate clastic sourced illite and chlorite in the samples, probably due to the weathering of volcanic ash and glass in an aqueous transport and depositional environment. However, the chondrite-normalized REE plot of mudrocks of the Asara Shale show a similarity with the UCC composition. Mineral composition and geochemistry of the Asara Shale mudrocks reveal the rapid reworking of penecontemporaneous volcaniclastic deposits, which had covered the surrounding areas, instead of their epiclastic genesis related to erosion and transport. Major, trace, and rare earth element (REE) data, imply a felsic composition of the volcanic source, related to an active continental margin/continental island arc and most probably back-arc tectonic setting for the depositional basin, inferring a mid-upper Eocene extensional volcanism in a subduction complex. Highlights: Mineralogical and geochemical characterization of Asara Shale Member, Iran. Geochemical signatures of provenance relations. Felsic and intermediate volcanic rocks as main source rocks. Eocene arc-related active volcanism in a subduction complex.